Improving seed systems for smallholder farmers' food security. Report of the mid-term workshop of the project - López Noriega, Isabel (2016)
The project "Improving Seed Systems for Smallholder Farmers' Food Security" aims to contribute to a future in which farmers successfully use crop diversity to ensure their food security and that of their communities, to thrive in challenging conditions and to make their farms resilient. The project addresses to particular issues vital to this goal: i) crop diversity available for farmers through seed systems; and ii) the policies that regulate such systems. The project is funded by the Swiss Development and Cooperation Agency, coordinated by Bioversity International and carried out in Bolivia, Burkina Faso, Nepal, Uganda and Uzbekistan. The project started in 2012. In October 2015, one year before the ending date of the project, Bioversity International and the Nepali organization LI-BIRD organized a project-wide workshop in Pokhara, Nepal, with the following objectives: To exchange experiences and share approaches and methods that have been tested during the life of the project; to review advances in project implementation in each of the countries and prioritize remaining activities; to discuss and agree on project-wide products that can be promoted at international level to allow project results to scale up; and to identify areas of work for a possible second phase of the project. This report presents the main discussions held at the workshop and the agreed actions.